(untitled) (Research, Society and Development, 2022)
The effect of potassium levels (0, 50, 100 and 200 kg of K2O ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics of Mesosetum chaseae (Luces) was evaluated under natural field conditions. Potassium fertilization increased significantly (P<0.05) GDM yields, absolute growth rate (AGR), number of tillers/plant, number of leaves plant-1, medium blade length, leaf area, leaf senescence rate, leaf appearance and elongation rates. Maximum GDM yields, AGR, number of tillers/plant, number of leaves/tiller, leaf area and medium blade length were obtained with the application of 167.8; 156.2; 82.7; 101.6; 101.2 and 77.5 kg of K2O ha-1, respectively. The potassium efficiency utilization was inversely proportional to the increased potassium levels.